Opt-in consent policies: potential barriers to hospital health information exchange - Apathy, Nate C. (Am J Manag Care, 2020)
OBJECTIVES: First, to assess whether hospitals in states requiring explicit patient consent (“opt-in”) for health information exchange (HIE) are more likely to report regulatory barriers to HIE. Second, to analyze whether these policies correlate with hospital volume of HIE. STUDY DESIGN: Cross-sectional analysis of US non-federal acute care hospitals in 2016. METHODS: We combined legal scholarship surveying HIE-relevant state laws with the AHA Annual IT Supplement for regulatory barriers and hospital characteristics. Data from CMS reports for hospitals attesting to Meaningful Use Stage 2 in 2016 (MU2, renamed “Promoting Interoperability” in 2018) captured hospital HIE volume. We used multivariate logistic regression and linear regression to estimate the association between opt-in state consent policies and reported regulatory barriers and HIE volume, respectively. RESULTS: Hospitals in states with opt-in consent policies were 7.8 percentage points more likely than hospitals in opt-out states to report regulatory barriers to HIE (p=0.03). In subgroup analyses, this finding held among hospitals that did not attest to MU2 (7.7pp, p=0.02). Among hospitals attesting, we did not find a relationship between opt-in policies and regulatory barriers (8.0pp, p=0.13), nor evidence of a relationship between opt-in policies and HIE volume (ß=0.56, p=0.76). CONCLUSIONS: Our findings suggest that opt-in consent laws may carry greater administrative burdens compared to opt-out policies. However, less technologically advanced hospitals may bear more of this burden. Furthermore, opt-in policies may not impact HIE volume for hospitals that have already achieved a degree of technological sophistication. Policymakers should carefully consider the incidence of administrative burdens when crafting laws pertaining to HIE.